Concomitant allergic contact dermatitis and plaque psoriasis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
The frequency of psoriasis and allergic contact dermatitis (DAC) should lead to the concomitant presence of the two disorders in several cases. However, this occurs exceptionally in the clinical practice. Many reports studied the prevalence of contact sensitization in psoriasis (1, 3, 4), singling out groups of psoriatic subjects -with palmo-plantar involvement- at higher risk of sensitization (1) or underlining the greater frequency of sensitization against topical drugs such as dithranol and fragrances (3). On the other hand, the reports regarding ACD in subject with psoriasis are exceptional (2), leading to hypothesize conflictual reaction mechanisms in the two disorders and underlining the difference between sensitization and clinically evident diasease.